The Concrete-Pictorial-Abstract Approach to the Achievement of Mathematics Learning Outcomes of Elementary School Students in terms of Early Mathematical Abilities - Yuliyanto, Aan; Hidayati, Novi; Syafitri, Yoesrina Novia Vini (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2023)
Low student mathematics learning outcomes should be a concern at this time, because low learning outcomes indicate that learning objectives have not been achieved. This study aimed to see how far the achievement of students' mathematics learning outcomes (MLO) is through the concrete-pictorial-abstract (CPA) approach based on students' early mathematical abilities (EMA). The study used a quasi-experimental through a nonequivalent pretest-posttest control group design. One hundred nineteen 5th-grade elementary school students in Purwakarta, Subang, Karawang, and Bekasi districts participated in this study on the volume of cubes and rectangular prisms. The research instrument used tests and non-tests, which were analyzed with descriptive and inferential statistics. The findings show that the achievement of MLO of students who receive learning with the CPA approach is better than conventional learning (CPA: 64,32 and Conventional: 56,32) p-value 0,001<0,05. Achievement of students' MLO in learning CPA and conventional in the high EMA group is in the high category (CPA: 75,31 and Conventional: 78,00) p-value 0,343>0,05. Achievement of students' MLO in learning CPA and conventional in the Moderate EMA group is in the medium category (CPA: 61,62 and Conventional: 51,54) p-value 0,003<0,05. Achievement of students' MLO in learning CPA and conventional in the Low EMA group is in the medium category (CPA: 55,00 and Conventional: 36,36) p-value 0,012<0,05. Thus, the concrete-pictorial-abstract approach can be an alternative to developing MLO for students with high, medium, or low mathematical abilities.